Central nervous system tumours in children in Ibadan, Nigeria: a histopathologic study (2016)
Introduction: Contrary to some earlier teachings that central nervous system (CNS) tumours are uncommon in black children, these neoplasms are the fourth most common paediatric tumours in Ibadan. Our centre is the major referral centre for CNS tumours in Nigeria. The last major study of paediatric CNS neoplasms from Ibadan was in 1985. An update of the data on paediatric CNS neoplasms at our centre is presented. Methods: A retrospective review of all histologically diagnosed CNS tumours in children (0-14 years) from January 2001 to December 2010 from the database of the Department of Pathology, University College Hospital, Ibadan, Nigeria was done. The cases were classified using the 2007 WHO Classification of Tumours of the Central Nervous System and were also based on their supratentorial and infratentorial locations. Results: Seventy-seven tumours, 44 in males, were included in the study. Astrocytic tumour comprised 20 cases, embryonal tumours 15, ependymal tumours 15, germ cell tumours 6, sellar tumours (all craniopharyngiomas) 9 and other histological types- 12 cases. Thirty-seven were WHO Grade 1, eleven Grade 2, ten Grade 3 and nineteen Grade 4 neoplasms. Thirty-six cases were supratentorial and thirty-eight were infratentorial in location. The most common tumours in this series were pilocytic astrocytomas, medulloblastomas, craniopharyngiomas and ependymomas in that order. Conclusion: Childhood CNS tumours are being increasingly diagnosed in our centre. This is largely explained by the recent expansion of the available neurosurgical services